Usability evaluation method for mobile learning application using agile: A systematic review - Hussain, Azham; Saleh, Abdulkarim; Taher, Abdussalam; Ahmed, Imman; Lammasha, Mohammed (Penerbit UTM Press, 2015)
The use of mobile phones for academic purpose has been on the rise in recent years.Most m-learning applications have been proved that they did not undergo usability evaluation while a few of the application underwent reliable usability evaluations.This paper reviews previous research that has been carried out to evaluate the usability of m-learning applications and how this approach could be integrated into the Agile development process in a bid to make a more effective and usable m-learning application. We focus on previous works that has been done in both, mobile application usability and integration of agile approaches for Usability evaluation.The incorporation of agile development processes and the usability evaluation of m-learning applications has produced a significant impact.This is seen as more m-learning applications are done in the sprints with the usability evaluation preceding it and following the development process which makes the applications more usable and user friendly.